On high Q(2) behavior of the pion form factor for transitions gamma*gamma -> pi(0) and gamma*gamma* -> pi(0) within the nonlocal quark-pion model - Anikin, IV; Dorokhov, A. E.; Tomio, L. (Elsevier B.V., 2000)
The behavior of the transition pion form factor for processes gamma (*)gamma --> pi(0) and gamma (*)gamma (*) --> pi(0) at large values of space-like photon momenta is estimated within the nonlocal covariant quark-pion model. It is shown that, in general, the coefficient of the leading asymptotic term depends dynamically on the ratio of the constituent quark mass and the average virtuality of quarks in the vacuum and kinematically on the ratio of photon virtualities. The kinematic dependence of the transition form factor allows us to obtain the relation between the pion light-cone distribution amplitude and the quark-pion vertex function. The dynamic dependence indicates that the transition form factor gamma (*)gamma -->, pi(0) at high momentum transfers is very sensitive to the nonlocality size of nonperturbative fluctuations in the QCD vacuum. (C) 2000 Elsevier B.V. B.V. All rights reserved.
Keywords: nonperturbative calculations; pion form factors; nonlocal theories and models